Analysis the Influence Factors and Deviation of Gas Outflow in Resumed Mine. Issue 4 (April 2020) - Dong, Wang; Hong, Ding
Abstract: In view of the problem of insufficient wind distribution basis during recovery, on the basis of analyzing the influence factors of gas outflow in the resumed mine, the research object is taken by the Limin coal mine in Hunan Province, and the gas excitant quantity prediction and deviation analysis are carried out in different production periods when the mine is produced by the source and statistics method. The results show that the mine relative gas outflow prediction error is 6.98 to 19.96 percent, controlled by coal seam thickness and gas content, mining depth geological conditions and other natural factors, while the mine absolute gas outflow prediction error is 20.89 to 44.01 percent, controlled by mining technology factors such as mining scale, recovery schedule and shutdown time.